A RARE CASE OF TOTAL ANOMALOUS PULMONARY VENOUS CONNECTION: CASE REPORT AND LITERATURE REVIEW - Plotski, A. R.; Siarhei, E. A.; Lupachik, E. I.; Kononov, V. N. (Zhurnal Grodnenskogo gosudarstvennogo medit͡s︡inskogo universiteta, 2025)
Congenital heart disease is a leading cause of infant morbidity and mortality. Only one half of congenital cardiac anomalies are identiﬁed before the birth of a child. Total anomalous pulmonary venous connection is characterized by the pulmonary veins failing to connect to the left atrium. A case of a rare congenital heart defect – infracardiac type of total anomalous pulmonary venous connection – is presented. Congenital heart defect was not detected either in the antenatal period or after the child's birth. The diagnosis was made after the death of the child at the age of 3 months and 3 days. The possibility of survival during this time was associated with a significant size of the atrial septal defect. A review of the literature is provided with an emphasis on changes in approaches to prenatal diagnosis of congenital heart defects, as well as on the possibility of surgical correction of total anomalous pulmonary venous connection. Successful treatment of patients with total anomalous pulmonary venous connection is possible in case of accurate prenatal diagnosis and improvement of both surgical techniques and perioperative management.